The influence of the literacy environment on children’s writing development in Chinese - Su, Mengmeng; Fan, Yi; Wu, Jifeng; Qiao, Bingyan; Zhou, Wei (Frontiers in Psychology, 2022)
The present study investigated the influence of literacy environment on the performance of writing narratives for primary school students. Two hundred and fifty Chinese children participated in this study. There were 146 third graders (71 boys and 75 girls) and 104 fifth graders (53 boys and 51 girls). Results showed that children’s writing abilities differed at the word level and sentence level between third grade and fifth grade. Formal literacy experience (parent teaching of characters) predicted the writing performance of third graders, while informal literacy experience (the visiting frequency of various places) predicted the writing performance of fifth graders. After controlling the effect of reading efficiency on the writing skills, the prediction of formal and informal literacy experiences on the writing performance remained. The results suggest the importance of formal and informal literacy experiences on the writing development of primary school students.